2021
DOI: 10.1038/s41598-021-90430-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of continuous apical negative ultrasonic irrigation (CANUI) in penetration of simulated lateral canals in extracted teeth

Abstract: The aim of this study was to evaluate the efficacy of continuous apical negative ultrasonic irrigation into simulated lateral canals and the apical third in straight and curved root canals. Two simulated lateral canals were created 2, 4 and 6 mm from the working length in 120 single-rooted teeth (6 canals/tooth, n = 360 straight, n = 360 curved). The teeth were randomly divided into 3 experimental groups: positive pressure irrigation (PPI) (n = 20); passive ultrasonic irrigation (PUI) (n = 20); continuous apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Following a title and abstract screening, 23 studies were found to be eligible for full-text evaluation. A total of 12 studies were selected to include in the systematic review ( Castelo-Baz et al, 2021 , Castelo-Baz et al, 2016 , Castelo-Baz et al, 2012 , de Gregorio et al, 2012 , de Gregorio et al, 2010 , de Gregorio et al, 2009 , Kanumuru et al, 2015 , Khare and Suprabha, 2017 , Pawar et al, 2013 , Souza et al, 2019 , Spoorthy et al, 2013 , Yaghi and Kaloustian, 2016 ), with the omission of 11 studies. The reasons for the exclusion are outlined in Appendix C. A total of 10 studies were qualified for inclusion in the meta -analysis ( Castelo-Baz et al, 2021 , Castelo-Baz et al, 2016 , Castelo-Baz et al, 2012 , de Gregorio et al, 2012 , de Gregorio et al, 2010 , Khare and Suprabha, 2017 , Pawar et al, 2013 , Souza et al, 2019 , Spoorthy et al, 2013 , Yaghi and Kaloustian, 2016 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a title and abstract screening, 23 studies were found to be eligible for full-text evaluation. A total of 12 studies were selected to include in the systematic review ( Castelo-Baz et al, 2021 , Castelo-Baz et al, 2016 , Castelo-Baz et al, 2012 , de Gregorio et al, 2012 , de Gregorio et al, 2010 , de Gregorio et al, 2009 , Kanumuru et al, 2015 , Khare and Suprabha, 2017 , Pawar et al, 2013 , Souza et al, 2019 , Spoorthy et al, 2013 , Yaghi and Kaloustian, 2016 ), with the omission of 11 studies. The reasons for the exclusion are outlined in Appendix C. A total of 10 studies were qualified for inclusion in the meta -analysis ( Castelo-Baz et al, 2021 , Castelo-Baz et al, 2016 , Castelo-Baz et al, 2012 , de Gregorio et al, 2012 , de Gregorio et al, 2010 , Khare and Suprabha, 2017 , Pawar et al, 2013 , Souza et al, 2019 , Spoorthy et al, 2013 , Yaghi and Kaloustian, 2016 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Study IATs No. of teeth Number of lateral canals n (%) 2 mm 4 mm 4.5 mm 6 mm Overall Straight canals Castelo-Baz et al, 2021 CNI 20 0 (0) 0 (0) 0 (0) 0 (0) PUI 20 15 (37.5) 10 (25) 15 (37.5) 40 (33.3) Souza et al, 2019 CNI 20 2 (5) 4 (10) 13 (32.5) 19 (15.8) PUI 20 26 (65) 29 (72.5) 34 (85) 89 (74.2) Kanumuru et al, 2015 CNI 15 0 (0) 8 (26.6) 16 (53.3) 24(26.7) PUI 15 30 (1 0 0) 30 (1 0 0) 30 (1 0 0) 90 (1 0 0) SI 15 14 (46.7) 18 (60) 30 (1 0 0) 62 (68.9) Pawar et al, 2013 CNI 20 0 (0) 0 (0) 0 (0) 0 (0) PUI 20 28 (70) 40 (1 0 0) 40 (1 0 0) 108 (90) SI 20 0 (0) 4 (10) 6 (15) 10 (8.3) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to previous alternative approaches to root canal disinfection such as continuous apical negative ultrasonic irrigation [18,19], high-frequency electrical pulses [20], electric current and silver electrodes [21] as well as Er:YAG laser irradiation [22], BDD electrodes led to a decrease in bacterial count but could not predictably prevent bacterial regrowth [23] under clinical conditions.…”
Section: Discussionmentioning
confidence: 95%
“…However, it has recently been shown for ultrasonic activation systems to cause smear layers in the apical parts of the canal system [16], counteracting the desire of removing bacterial biofilms, which are more resistant than their planktonic counterparts [17]. In addition, a wide variety of advanced treatment modalities have been introduced including continuous apical negative ultrasonic irrigation [18,19], highfrequency electrical pulses [20], electric current and silver electrodes [21] as well as Er:YAG laser irradiation [22]. Most of these techniques result in a decrease in bacterial numbers but cannot predictably prevent bacterial regrowth [23].…”
Section: Introductionmentioning
confidence: 99%